Effect of nano zinc oxide or chelated zinc as alternatives to medical zinc oxide on growth performance, faecal scores, nutrient digestibility, blood profiles and faecal Escherichia coli and Lactobacillus concentrations in weaned piglets - Han Jin Oh; Myung Hoo Kim; Won Yun; Ji Hwan Lee; Ji Seon An; Yong Ju Kim; Min Ji Kim; Hyeun bum Kim; Jin Ho Cho (Italian Journal of Animal Science, 2022)
A total of 144 weaned piglets (6.80 ± 0.46 kg, [Landrace × Yorkshire] × Duroc) were used in a 4-week feeding trial to determine the effect of nano zinc oxide or chelated zinc as alternatives to medical zinc oxide (ZnO) in weaned piglets. The pigs were randomly distributed to one of 6 treatment groups (4 pigs in a pen, 6 replicate pens per treatment). The dietary treatments were negative control (NC), no additional zinc oxide in the diet; positive control (PC), NC + 2500 mg/kg ZnO; 100 mg Chelate (NC + 100 zinc chelate); 200 mg Chelate (NC + 200 mg/kg of zinc chelate); 100 mg Nano (NC + 100 mg/kg ZnO nanoparticles), and 200 mg Nano (NC + 200 mg/kg nanoparticles). The growth performance of pigs fed the PC and Nano diets were significantly higher than that of pigs in the Chelate treatment groups (p < .05). In the overall periods, the faecal scores were significantly increased (p < .05) in the PC treatment group compared to the 100 mg/kg Chelate and Nano treatment groups. The apparent total tract digestibility (ATTD) of crude protein and faecal Lactobacillus concentrations were significantly decreased (p < .05) in the NC group compared to the other groups. The ATTD of zinc was significantly increased (p < .05) in the Chelate treatment groups compared to the other treatment groups. In conclusion, 200 mg/kg Nano showed similar effects on growth performance, nutrient digestibility, and faecal Lactobacillus concentrations in weaning pigs as medical ZnO.HIGHLIGHTS To evaluate the effects of nano zinc oxide or chelated zinc as an alternative to medical zinc oxide in weaned piglets High-dose zinc oxide and 200 mg/kg zinc oxide nanoparticle supplementation showed beneficial effects on growth performance and crude protein digestibility Supplementation with zinc chelated with glycine resulted in significantly higher (p < .01) the ATTD of zinc than other treatments groups. Faecal Lactobacillus concentrations were significantly decreased (p < .05) in the no additional zinc oxide diet group compared to the other treatment groups. Nano-ZnO at 100 or 200 mg/kg had similar effects on growth performance and nutrient digestibility with lower zinc excretion than that of weaned pigs given medical zinc oxide.